En kognitiv semantisk analys av SAOB:s formler för betydelseförändring - Nilsson, Pär (Nordiske Studier i Leksikografi, 2018)
In my dissertation the method to describe semantic change used in the Swedish Academy dictionary (SAOB) is compared with cognitive semantic models of such a change. The work of SAOB is theoretically unbound in terms of overarching semantic theories, and the methods of describing word meaning and semantic change in the dictionary are rather developed for pragmatic reasons (such as consistency and economy etc.). The first volume of SAOB was published in 1898 and the latest in 2012. A lot has happened during this time within lexicographic theory as well as in general linguistics. To SAOB editors today the view of language and linguistics is to a large extent unlike the one the editors had in the late nineteenth century. Despite this fact the principles behind structuring and representing semantic information in the dictionary seem to have a lot in common with the theory based discussion in contemporary literature in the cognitive field. My starting point is to analyze the structure of articles in SAOB, in particular the use of specific labels used in the definitions, such as bildl. (figurative), utvidgdad anv. (extended use) etc. My aim is to evaluate the pragmatic SAOB model and to investigate to what extent it can be interpreted to represent the way humans structure and categorize language and linguistic meaning. In this presentation I will demonstrate examples of how the SAOB method can be transferred to and interpreted through models derived from cognitive semantics.